Perancangan media interaktif film pendek “Jerat (2022)” dalam realitas virtual untuk UCIFEST 14 - Siti Adlina Rahmiaty; Fachrul Fadly; Vimala Dharma Santi; Angela Arthasevia Hardinata; Quenna Mutiara Chriesty; Cindy Buntoro; Daniel Osvaldo Rahmanto; Wahyu Dwi Santoso (Asosiasi Dosen Pemerhati Pendidikan Indonesia, 2023)
This research is intended to be a guide to the process of designing interactive applications needed in virtual reality as a new experience of watching movies. The campus film festival, UCIFEST 14 (UMN Cinema Festival) is one of the competitions that provides an opportunity to display moving image works by utilizing new media such as virtual reality. To be able to watch a 360-degree video, a device such as an HMD (Head-Mounted Display) and an application in it that displays a film program are needed. This research uses a qualitative method with field observations to collect data by utilizing the MDLC (Multimedia Development Life Cycle) concept and the Unity3D application. The final result of this research is an interactive media application for the short film